How do H2 oxidation molecular catalysts assemble onto carbon nanotube electrodes? A crosstalk between electrochemical and multi-physical characterization techniques. Issue 48 (29th November 2021) - Ghedjatti, Ahmed; Coutard, Nathan; Calvillo, Laura; Granozzi, Gaetano; Reuillard, Bertrand; Artero, Vincent; Guetaz, Laure; Lyonnard, Sandrine; Okuno, Hanako; Chenevier, Pascale
Abstract : How do efficient hydrogen-oxidation molecular electrocatalysts connect onto their carbon nanotube conductive support? A coupled neutron scattering SANS and STEM electron microscopy study to observe soft active matter organizing on 3D nanosurfaces. Abstract : Molecular catalysts show powerful catalytic efficiency and unsurpassed selectivity in many reactions of interest. As their implementation in electrocatalytic devices requires their immobilization onto a conductive support, controlling the grafting chemistry and its impact on their distribution at the surface of this support within the catalytic layer is key to enhancing and stabilizing the current they produce. This study focuses on molecular bioinspired nickel catalysts for hydrogen oxidation, bound to carbon nanotubes, a conductive support with high specific area. We couple advanced analysis by transmission electron microscopy (TEM), for direct imaging of the catalyst layer on individual nanotubes, and small angle neutron scattering (SANS), for indirect observation of structural features in a relevant aqueous medium. Low-dose TEM imaging shows a homogeneous, mobile coverage of catalysts, likely as a monolayer coating the nanotubes, while SANS unveils a regular nanostructure in the catalyst distribution on the surface with agglomerates that could be imaged by TEM upon aging. Together, electrochemistry, TEM and SANS analyses allowed drawing an unprecedented and intriguing picture with molecular catalysts evenly distributed at the nanoscale in two different populations required for optimal catalytic performance.